Pelatihan Desain Video Pembelajaran untuk Meningkatkan Kompetensi Guru dalam Membuat Media Pembelajaran - Muhammad Sayyadi; Moh Ahsan (jurnal ABDIMAS Indonesia, 2024)
Teachers have an important role to produce the next generation of the nation. Future teachers need to keep up with technological developments in learning. One of the technologies needed in learning is designing learning media with the help of sparkol videoscribe. Sparkol videoscribe serves as an intuitive tool for creating animated whiteboards and explainer videos. The implementation of the workshop consists of 5 stages of preparation, mentoring, making videos with the sparkol videoscribe application, validating the resulting learning videos and improving the videos until they are suitable for use. This activity was attended by KKG cluster one Saparua District, Central Maluku. The result obtained in this service is that the teachers gave a positive response regarding this activity. Teacher competence in making media in the form of learning videos obtained results as much as 75% suitable for use, but after there was an improvement increased to 93% of the learning videos produced suitable for use.